Proteomics of the wheat tan spot pathogen Pyrenophora tritici-repentis 06 Biological Sciences 0607 Plant Biology - Moffat, Caroline; Stoll, T.; Moolhuijzen, Paula (BioMed Central, 2018)
Objectives: The fungus Pyrenophora tritici-repentis is a major pathogen of wheat worldwide, causing the leaf spotting disease tan spot. To best inform approaches for plant genetic resistance, an understanding of the biology and pathogenicity mechanisms of this fungal pathogen is essential. Here, intracellular and extracellular proteins of P. tritici-repentis were extracted, and peptides analysed via high-resolution mass spectrometry. Our objective was to generate a useful proteomics resource for P. tritici-repentis. A survey of proteins secreted by the pathogen into culture filtrate is especially useful, as these are likely to come in direct contact with the wheat host and may play important roles in infection/pathogenicity. The peptide data presented herein, has also been used to successfully verify and refine in silico predicted P. tritici-repentis gene annotations, through the validation of alternative splicing and reading frame shifts. Data description: The data sets presented consist of peptide spectra of the extracellular and intracellular proteomes of three P. tritici-repentis isolates. Peptide matches to translated transcripts of the North American reference isolate Pt-1C-BFP are also provided.